Environmental Psychology Approach: Understanding Tourist’s Intention to Reducing Food Waste in Badung Regency, Bali, Indonesia - Indah Andesta (Gadjah Mada Journal of Tourism Studies, 2019)
Bali is one of the destinations with the highest tourist visiting in Indonesia. One concern is food waste produced by tourists during the holiday. Most of the food waste comes from consumers level. Thus, needed to understand what factors influence of tourist’s intention to reduce food waste during the holiday. This study aims to understand tourist behavioural intention of reducing food waste during the holiday. The conceptual model was built based on the new environmental paradigm scale and environmental psychology approach. There are six hypotheses designed through environmental attitude, feeling personal responsibility, knowledge and intention to reduce food waste during vocation. Correlation and multiple regression were chosen to analyse the data. Environmental attitude did not have a direct association of tourist’s intention to reduce food waste (p-value=.23). Meanwhile, feeling personal responsibility and knowledge to reduce food waste has a significant relationship with the outcome (p-value=.001). In the environmental attitude, both local and foreign tourists are not profoundly correlated with the understanding of tourist’s intention to reduce food waste during the holiday. Overall, the study concludes that tourists can figure out the intention of reducing food waste, even though they do not concern about general environmental attitude.